Correlation of Pelvic Organ Prolapse Quantification Technique with Pelvic Floor Dysfunction Symptoms - Pradhan, Tarun; Rijal, Pappu; Thapa, Baburam Dixit; Bhatta, Rabindra Dev; Hakkim, Mohsina; Rai, Rubina (Birat Journal of Health Sciences, 2019)
Introduction: Assessment of POP by POP-Q gives anatomical site-specific measurement, which helps in surgery, follow-up and reduces inter-observer variation. The Pelvic Floor Distress Inventory (PFDI) is condition-specific health-related quality of life questionnaires for women with pelvic floor disorders.Objective: To assess pelvic organ prolapse by POP-Q technique and to correlate pelvic floor distress inventory questionnaire with POP-Q segments. Methodology A prospective study was done from March 2014 to February 2015 after ethical approval from IRC, B.P. Koirala Institute of Health Sciences. All patients with pelvic organ prolapse were included after informed verbal consent. The patients were then asked questions as in pelvic floor distress inventory questionnaire (PFDI) and noted in performa. The patients were then examined by POP-Q technique and noted. The informations were entered in the MS excel chart and statistical analysis done using SPSS 11.5.Results: There were 72 patients enrolled. The mean age of patients was 53.65 years. Majority of patients were found to have stage 4 prolapse (43.1%). POP-Q examination showed majority of patients had anterior and apical compartment defect. Correlation between POP-Q points and urinary symptoms showed significant relation with points in anterior compartment, genital hiatus and perineal bodies. Correlation with POP-Q points with colorectal symptoms showed involvement of genital hiatus significantly with strain stool and incomplete bowel movement. Correlation with pelvic distress symptoms with POP-Q sites showed significant relation with bulging, push up vagina for urination and defecation.Conclusion: POP-Q site specific points showed significant correlation with symptoms from Pelvic Floor Distress Inventry (PFDI) questionnaires.